Non-attached deputies in the labyrinth. Commentary to S.T.C. 159/2019, of december 12 - Greciet García, Esteban (Journal of the Basque Parliament, 2020)
This paper comments the first judgment of the Spanish Constitutional Court that resolves an appeal for protection brought by a Deputy not attached by the rights and powers that had been attributed to him, as such, in an autonomous Parliament, and relates his legal situation with the solutions that the House Rules and legislation try to give to ideological disaffection and the phenomenon of transfuguism, as an anomaly in the relationship of political representation.